Which Patients have Greatest Need for Elvitegravir/Cobicistat/ Emtricitabine/TenofovirDF-Based Therapy? - Di Biagio, Antonio; Prinapori, Roberta; Taramasso, Lucia; Gustinetti, Giulia; Sticchi, Laura; Bruzzone, Bianca; Viscoli, Claudio (Recent Patents on Anti-Infective Drug Discovery, 2014)
Elvitegravir/cobicistat/emtricitabine/tenofovirDF (EVG/COBI/FTC/TDF) is the new single-tablet, fixed-dose formulation containing an integrase strand transfer inhibitor recently approved as antiretroviral treatment. In this paper we analysed its use and advantages in naïve and experienced HIV-infected patients and we focused on special populations in which EVG/COBI/FTC/TDF could be a suitable option. Furthermore the manuscript reports the recent patent of EVG which may have an influence on the management of HIV-infected patients in the next future.
Keywords: tenofovirDF